Immunogenicity and safety of a cell culture-based quadrivalent influenza vaccine in adults: A Phase III, double-blind, multicenter, randomized, non-inferiority study. Issue 9 (1st September 2016) - Bart, Stephan; Cannon, Kevin; Herrington, Darrell; Mills, Richard; Forleo-Neto, Eduardo; Lindert, Kelly; Abdul Mateen, Ahmed
ABSTRACT: Quadrivalent influenza vaccines (QIVs), which include both B lineage strains, are expected to provide broader protection than trivalent influenza vaccines (TIVs). The non-inferiority, immunogenicity, and safety of a cell culture-based investigational QIVc and 2 TIVs (TIV1c, TIV2c), in adults (≥18 y), were evaluated in this Phase III, double-blind, multicenter study. A total of 2680 age-stratified subjects were randomized (2:1:1) to receive 1 dose of QIVc (n = 1335), TIV1c (n = 676), or TIV2c (n = 669). TIV1c (B/Yamagata) and TIV2c (B/Victoria) differed only in B strain lineage. The primary objective was to demonstrate non-inferiority of the hemagglutinin-inhibition antibody responses of QIVc against TIVc, 22 d post-vaccination. Secondary objectives included the evaluation of immunogenicity of QIVc and TIVc in younger (≥18 – <65 y) and older (≥65 y) adults. Hemagglutinin inhibition assays were performed at days 1 and 22. Solicited local and systemic adverse events (AEs) were monitored for 7 d post-vaccination, and unsolicited AEs and serious AEs until day 181. QIVc met the non-inferiority criteria for all 4 vaccine strains and demonstrated superiority for both influenza B strains over the unmatched B strain included in the TIV1c and TIV2c, when geometric mean titers and seroconversion rates with TIVc were compared at day 22. Between 48%–52% of subjects experienced ≥1 solicited AE, the most common being injection-site pain and headache. Serious AEs were reported by ≤1% of subjects, none were vaccine-related. The results indicate that QIVc is immunogenic and well tolerated in both younger and older adults. The immunogenicity and safety profiles of QIVc and TIVc were comparable at all ages evaluated.